Konrad Raiser: The Challenge of Transformation. Issue 1 (14th March 2018) - Robra, Martin
Abstract: This article discusses the role played by Konrad Raiser in the World Council of Churches (WCC), from 1969, when he joined the staff as a study secretary, to his time as general secretary from 1993 to 2003, and especially his role in the conciliar process for Justice, Peace, and the Integrity of Creation. As general secretary, Raiser played a key role in supporting and encouraging the churches' witness for peace and nonviolence, strengthening the fellowship of churches within the WCC through the process to develop a "Common Understanding and Vision" and the Special Commission on Orthodox Participation in the WCC.